Recurrence and influencing factors of hepatitis B surface antigen seroclearance induced by peginterferon alpha-based regimens - Lu, Rui; Zhang, Meng; Liu, Zi-Han; Hao, Miao; Tian, Yan; Li, Mei; Wu, Feng-Ping; Wang, Wen-Jun; Shi, Juan-Juan; Zhang, Xin; Jia, Xiao-Li; Jiang, Zi-Cheng; et al. (World journal of gastroenterology : WJG, 2024)
BACKGROUND The long-term stability of hepatitis B surface antigen (HBsAg) seroclearance following peginterferon alpha (peg-IFN-α)-based therapy has not been extensively studied, leaving the full potential and limitations of this strategy unclear. AIM To assess HBsAg recurrence after seroclearance achieved by peg-IFN-α regimens. METHODS This prospective, multicenter, observational study was conducted from November 2015 to June 2021 at three Chinese hospitals: The Second Affiliated Hospital of Xi’an Jiaotong University, Ankang Central Hospital, and The Affiliated Hospital of Yan’an University. Participants who achieved HBsAg seroclearance following peg-IFN-α-based treatments were monitored every 4-12 weeks post-treatment for hepatitis B virus (HBV) markers, HBV DNA, and liver function. The primary outcome was HBV recurrence, defined as the reemergence of HBsAg, HBV DNA, or both, at least twice within 4-8 weeks of follow-up. RESULTS In total, 121 patients who achieved HBsAg seroclearance were enrolled. After a median follow-up of 84.0 (48.0, 132.0) weeks, four subjects were lost to follow-up. HBsAg recurrence was detected in 16 patients. The cumulative HBsAg recurrence rate in the intention-to-treat population was 15.2%. Multivariate logistic regression analysis demonstrated that consolidation time < 12 weeks [odds ratio (OR) = 28.044, 95%CI: 4.525-173.791] and hepatitis B surface antibody disappearance during follow-up (OR = 46.445, 95%CI: 2.571-838.957) were strong predictors of HBsAg recurrence. HBV DNA positivity and decompensation of liver cirrhosis and hepatocellular carcinoma were not observed. CONCLUSION HBsAg seroclearance following peg-IFN-α treatment was durable over 84 weeks of follow-up with a cumulative recurrence rate of 15.2%.